Development of Pop-Up Book Learning Media for the Science and Social Studies (IPAS) Subject on the Topic of Energy in Everyday Life for Fourth Grade Students at SD Negeri 044825 Berastagi, Academic Year 2025/2026 - Emia Lestari br Sitepu; Jainal Togatorop; Yosefo Gule (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to develop a Pop-Up Book learning medium for the Natural and Social Sciences (IPAS) subject on the topic of energy in daily life, and to describe its validity and practicality for fourth-grade elementary school students. The study was motivated by students' low learning enthusiasm and the limited availability of concrete, interactive instructional media. This research employed the Research and Development (R&D) method using the PPE (Planning, Production, Evaluation) development model. The subjects were 23 fourth-grade students of SD Negeri 044825 Gundaling I Berastagi. Data were collected through observation, unstructured interviews, and questionnaires, then analyzed quantitatively using a Likert scale and qualitatively using the Miles and Huberman technique. The results show that the developed Pop-Up Book medium was valid, with validation scores of 97.5% from the content expert, 96.6% from the media expert, and 97.5% from the learning practitioner. The product trial showed positive student responses regarding attractiveness, ease of use, and the medium's contribution to understanding the concept of energy, with practicality percentages ranging from 83.9% to 93.7%. The Pop-Up Book medium was shown to shift the learning orientation from teacher-centered to student-centered, increase learning enthusiasm, and help transform abstract concepts into more concrete ones. This medium is recommended as a valid, practical, and enjoyable alternative instructional medium for IPAS learning in elementary schools.